Tata kelola inovasi pelayanan publik: dimensi kelembagaan, aktor kebijakan dan masyarakat - Siti Nur Hapzah; Budi Rianto; M Husni Tamrin (Universitas Merdeka Malang, 2020)
The goal of this research is to identify the innovation governance of 6-in-1 program in services for population affairs at the Autonomous Agency for Population Affairs and Civil Registry of Surabaya City Administration. Innovation of 6-in-1 program is an innovation containing the 6 products of population services (birth, death, moving, arriving, marriage, divorce). This research applies the Innovation Governance Theory from the United Nation, namely Institution, Policy Actor and Community in subsequent management, then elaborated by using the Theory of Cook and Mathews, namely Risk Management and Technology. This research applies “qualitative descriptive method‟ .The technique in determining the informant is classified into 2 (two) sample takings, the purposive sampling and the snowball sampling. Data are collected through observation interview, and documentation. The triangulation technique is used for verification or checking. Output of this research reveals that the innovation management must be supported by various aspects, such as the supporting policy, level of employees‟ compliance, community serving attitude, synergy among the stakeholders, culture, and community participation. However, there are still several things not yet been supportive, namely knowledge of the community, network technology and prevention management